sj-pdf-1-rci-10.1177_1745499921991958 – Supplemental material for Inclusive education in the diversifying environments of Finland, Iceland and the Netherlands: A multilingual systematic review ... - Wolff, Charlotte E.; Magnúsdóttir, Berglind Rós; Huilla, Heidi; Kosunen, Sonja; Tzaninis, Yannis; Paulle, Bowen; Lappalainen, Sirpa; Seppänen, Piia (SAGE Journals, 2021)
Supplemental material, sj-pdf-1-rci-10.1177_1745499921991958 for Inclusive education in the diversifying environments of Finland, Iceland and the Netherlands: A multilingual systematic review by Charlotte E. Wolff, Berglind Rós Magnúsdóttir, Heidi Huilla, Sonja Kosunen, Yannis Tzaninis, Bowen Paulle, Sirpa Lappalainen and Piia Seppänen in Research in Comparative and International Education ...